An expeditious synthesis of 3,4-dihydrobenzo[2,3-d]pyrimidines using inorganic solid supports - AKKAL DEO MISHRA; MAZAAHIR KIDWAI (Journal of the Serbian Chemical Society, 2004)
A series of novel 5-substituted-8-cyano-4,6,7-triphenyl-3,4-dihydrobenzo [2,3-d]pyrimidines were synthesized by the condensation of 6-substituted-2-amino-1-benzoyl-3-cyano-5-hydroxy-4,5-diphenyl-1,3-cyclohexadiene and formamide, using inorganic solid supports under microwaves. Some of the compounds were found to be effective against some fungal and bacterial strains.